Properties of Fr-like Th3+ from spectroscopy of high-L Rydberg levels of Th2+ - Keele, Julie A.; Hanni, M. E.; Woods, Shannon L.; Lundeen, S. R.; Fehrenbach, C. W. (My University, 2011)
Binding energies of high-L Rydberg states (L ⩾ 7) of Th2+ with n = 27–29 were studied using the resonant excitation Stark ionization spectroscopy (RESIS) method. The core of the Th2+ Rydberg ion is the Fr-like ion Th3+ whose ground state is a 5 2F5/2 level. The large-core angular momentum results in a complex Rydberg fine-structure pattern consisting of six levels for each value of L that is only partially resolved in the RESIS excitation spectrum. The pattern is further complicated, especially for the relatively-low-L levels, by strong nonadiabatic effects due to the low-lying 6d levels. Analysis of the observed RESIS spectra leads to determination of five properties of the Th3+ ion: its electric quadrupole moment Q = 0.54(4); its adiabatic scalar and tensor dipole polarizabilities αd,0 = 15.42(17) and αd,2 = -3.6(1.3); and the dipole matrix elements connecting the ground 5 2F5/2 level to the low-lying 6 2D3/2 and 6 2D5/2 levels, ∣∣⟨52F5/2∣∣∣∣D∣∣∣∣62D3/2⟩∣∣=1.435(10) and ∣∣⟨52F5/2∣∣∣∣D∣∣∣∣62D5/2⟩∣∣=0.414(24). All are in atomic units. These are compared with theoretical calculations.